(untitled) (University of Khartoum Engineering Journal, 2022)
This paper, evaluates the effects of the conventional laboratory compaction methods on gradation, plasticity, shrinkage and strength of natural unbound materials. Three different trial sections were constructed accompanied with field and laboratory tests to study and evaluate the most suitable compaction methods that simulate field compaction. The materials used in this investigation are colluvial deposits originally conglomerates belonging to Nubian Sandstone Formation. Experimental testing programs comprising two different activities were conducted, firstly: routine tests, Los Angeles abrasion, and CBR and secondly three field trial sections were constructed using field compaction equipment. The test results have shown that impact hammer resulted in more breakage of coarse particles and finer products compared to the other two methods. The measured strength after impact compaction was very high whereas the measured strength was low for the gyratory compaction method. The three field tests have shown that the gyratory compaction method simulated better field conditions. The impact compaction normally used for the estimation of the CBR of earthen pavement materials and highly overestimates the strength of these natural unbound materials.